Mother trucker : finding joy on the loneliest road in America - Butcher, Amy, 1987- (Little A, 2021)
Amy Butcher was an accomplished college professor, mentor, and writer, but in her own home, she was embarrassed and emotionally burdened by an increasingly abusive relationship. Exhausted and terrified, Amy reached out to Instagram celebrity Joy "Mothertrucker" Wiebe - the nation's only female ice road trucker. Invited by Joy to ride shotgun, Amy found her escape on a road that was treacherous, beautiful, and exhilarating - an adventurous ride through the Alaskan wilderness that was profoundly life changing.